ANALYSIS OF GROUNDWATER POTENTIAL USING THE WENNER CONFIGURATION RESISTIVITY GEOELECTRIC METHOD IN THE WATUBANGGA AREA, KOLAKA, SOUTHEAST SULAWESI - Sahrul Sahrul Poalahi salu; Arif Arif; Aswar Muh Aswar (USN Kolaka, 2026)
Groundwater is a crucial water resource for meeting community needs, especially in the Watubangga District, which has limited surface water resources. Groundwater potential cannot be directly observed because it is located beneath the Earth's surface and is influenced by geological conditions, lithology, and subsurface structures. This study aims to analyze subsurface resistivity values using geoelectrical methods in the Watubangga District area. It also aims to determine the depth and rock layers that indicate the presence of aquifer zones. It also analyzes the lateral and vertical distribution of the water-saturated layer (aquifer zone). The Wenner configuration is used in the geoelectrical resistivity method. The Wenner configuration is a widely used electrode configuration in the resistivity method due to its sensitivity to vertical layer changes. By measuring resistivity and interpreting the data using software such as RES2DINV, the distribution of resistivity values can be accurately mapped and provide an overview of subsurface geological conditions. The results showed that each track exhibited a variation in resistivity values, ranging from very low (10 ohm-m) to very high (100 ohm-m). These resistivity values are used to interpret the type and condition of subsurface rocks. The resistivity distribution displayed in the cross-section indicates conductive zones at the top and middle of the track, interpreted as water-saturated layers or aquifer zones. Conversely, high resistivity zones appear at the bottom, indicating bedrock or impermeable layers. Keywords: Aquifer, Geoelectricity, Groundwater, Resistivity, Watubangga District, Wenner Configuration